PENGARUH PENGGUNAAN BERBAGAI JENIS KABEL BUSI TERHADAP PERFORMA MESIN SKUTIK 108cc - Irwansyah Irwansyah; Muhammad Arsad Al Banjari; Feddy Wanditya Setiawan (Program Studi Teknik Otomotif, Politeknik Hasnur, 2021)
Ideally, the combustion system system in the combustion chamber, this is an alarm in order to get the right combustion results and of course will make the motorcycle power with the right fuel consumption too. There are at least 3 (three) important factors that must be met by the combustion system in the combustion motorbike, especially for gasoline-type automatic motorbikes. These three factors include the existence of an ideal fuel and air mixture (good air-fuel mixture), the right timing of business performance in producing spark plug spark quality (good spark) and good combustion chamber (good compression). An air-fuel mixture that can produce a homogeneous mixing of fuel and air. The acquisition of perfect combustion is directly proportional to the quality of a good type of spark plug cable. The ability of the type of spark plug cable must be able to support high electric current processes to produce the ideal spark. In this study, the type of business cable used is the brand that is in the market, namely proteck, extreme, hitachi and standard cable types. Performed variation testing 4 (four) types of spark plug cables. The test results show the best engine performance of a gasoline-fueled automatic motorbike using extreme spark plug cables, with a torque of 5,669 Nm at 7854 rpm and a power of 6,252 hp at 7854 rpm